2012
DOI: 10.1016/j.envint.2012.08.003
|View full text |Cite
|
Sign up to set email alerts
|

A novel abbreviation standard for organobromine, organochlorine and organophosphorus flame retardants and some characteristics of the chemicals

Abstract: Ever since the interest in organic environmental contaminants first emerged 50 years ago, there has been a need to present discussion of such chemicals and their transformation products using simple abbreviations so as to avoid the repetitive use of long chemical names. As the number of chemicals of concern has increased, the number of abbreviations has also increased dramatically, sometimes resulting in the use of different abbreviations for the same chemical. In this article, we propose abbreviations for fla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
160
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(167 citation statements)
references
References 32 publications
0
160
1
3
Order By: Relevance
“…Their structures are given in the Supporting Information (Table S-1, along with the offical abbreviation [21]). Stock solution of each was prepared at a concentration of 100 mg L À 1 in methanol and stored at 4 1C.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…Their structures are given in the Supporting Information (Table S-1, along with the offical abbreviation [21]). Stock solution of each was prepared at a concentration of 100 mg L À 1 in methanol and stored at 4 1C.…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…13−15 High-performance liquid chromatography coupled with tandem mass spectrometry (HPLC−MS/MS) and gas chromatography coupled with mass spectrometry (GC−MS) have been previously used to analyze some TBBPA derivatives. 11,12 In a previous study on TBBPA BAE and TBBPA BDBPE, Letcher et al applied HPLC coupled with atmospheric pressure photoionization (APPI) MS/MS as the analysis method. 13,15 A HPLC coupled with electrospray ionization (ESI) MS/MS method was also applied to determine TBBPA BAE in lake trout.…”
Section: ■ Introductionmentioning
confidence: 99%
“…TBBPA BDBPE is applied as an additive flame retardant in polyolefin resins and polystyrene. 4,11 Because of the large number of potential TBBPA analogues, there is still a need for developing sensitive analytical methods to investigate their environmental occurrence and distribution, 9 because these compounds could be environmentally persistent and have the potential for long-range atmospheric transport. 4 Although TBBPA has been widely studied, 12 only a few published studies have been reported on the analytical methodology, environmental behavior, and toxicity of TBBPA derivatives.…”
Section: ■ Introductionmentioning
confidence: 99%
“…2-Ethylhexyl-2,3,4,5-tetrabromobenzoate (EH-TBB) is lipophilic (logP est : 7.73-8.75) (Bergman et al, 2012;USEPA, 2016) and may cross membranes, but little is known about the disposition of EH-TBB in vivo for humans or animals. In vitro, EH-TBB was hydrolyzed to TBBA by esterases present in porcine intestine preparations, human and rat liver cytosol and microsomal protein, and rat serum .…”
mentioning
confidence: 99%